Dynamics of Foodgrain Deficiency in India. (November 2016) - Bhattacharya, Paramita; Mitra, Siddhartha; Siddiqui, Md. Zakaria
Food security is a basic requirement of livelihood. A major source of calories is carbohydrates which are mainly derived from foodgrains. This article addresses the foodgrain deficiency in India, across its states, regions and at the household level. The study further analyses the causal effect of subsidies from India's public distribution system, the share of home-produced foodgrain in total consumption of foodgrains, food diversification, monthly per capita consumption expenditure and socio-religious factors on foodgrain deficiency. The analysis is based on the National Sample Survey's unit-level data at three points of time: 1999–2000, 2004–05 and 2009–10. Foodgrain deficiency has been captured at the national level and across states by suitably adapting Foster, Greer and Thorbecke's (1984) measure of poverty. Panel regression has been done at the state-region level to analyse the impact of the above-mentioned determinants on foodgrain deficiency. For the household-level regression, the dependent variable is deviation from the desired norm of 8.6 kg of foodgrain per consumer unit per month. Quantile regression analysis is done at the household level to capture the impact of the determinants at different segments of foodgrain deviations. We find that foodgrain deficiency levels have increased for 'all-classes' and the 'below-poverty-level class' but the deficiency levels are not very high and can be managed with suitable measures. It is further found that the determinants have a significant influence on foodgrain deficiency and foodgrain deviation at the state-region and household levels, respectively. Suitable policy measures have also been identified. JEL Classification: I31, I32, C21, C23, O10, Q18